TYPES OF LEARNING APPLICATIONS KNOW ANIMALS USING MACROMEDIA FLASH MX VERSION 8.0 - Nanang Harianto; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2006)
This writing describes the information about different kinds of animals including animals that live on land, water, and air other than that I hope this application can be used as study materials. To learn more about the types of animals. so the author tries to specifically facilitate his parents to choose the type of education by presenting in the form of applications using Macromedia Flash MX version 8.0.